Effect of Sn plating thickness on wettability, solderability, and electrical connections of electronic lead connectors for surface mount technology applications - Maria Abu Bakar,; Mohamad Solehin Mohamed Sunar,; Azman Jalar,; Atiqah, A.; Fakhrozi Che Ani,; Ibrahym Ahmad,; Zol Effendi Zolkefli, (Penerbit Universiti Kebangsaan Malaysia, 2023)
The wettability of solder is important to achieve good solderability between the electronic component and printed circuit board (PCB). Tin (Sn) plating is widely used to promote the wettability of the solder on the substrates. However, an adequate amount of Sn plating thickness must be taken into consideration to acquire good wettability and solderability. Thus, this study investigates the Sn plating thickness of the electronic lead connector and their effect on the wettability and electrical connection. Two types of Sn plating thicknesses, ~3 μm, and 5 μm were applied on the electronic lead connector surface. It was found that the thin Sn plating thickness of ~3 μm has shown failure in electrical connections and lack of solder joint wettability and solderability properties. A thicker Sn plating thickness of 5 μm, has shown better wettability and solderability properties. In addition, the electrical connections also passed which implies that the thicker Sn plating thickness provides good solder joint establishment leading to good electrical connections. It is also observed that the better wettability of solder has been achieved for thicker Sn plating thickness. The finding from the field emission scanning electron microscope (FESEM) shows that the intermetallic compound (IMC) layer growth in the lead connector surface is regarded as abnormal for thin Sn plating thickness (~3 μm), in which the IMC layer was consumed and penetrating up to the surface of Sn-coating. This has led to poor solderability of the thin Sn plating with the solder to establish solder joint. The findings from this study have shed some light upon a better understanding of the importance of considering the adequate amount of Sn coating thickness to avoid IMC consumption at the Sn plating, better wettability properties, solderability, and solder joint quality for surface mount technology (SMT) especially for electronic lead connector applications.